2000
DOI: 10.1080/03601230009373273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imazaquin applications on the growth, leaf chlorophyll and yield of soybean in the Guinea Savanna of Nigeria

Abstract: Field trials were conducted during the wet seasons of 1989, 1991, 1994 and 1995 to evaluate the effects of pre-emergence and post-emergence applications of four rates of imazaquin (0.00; 0.15; 0.30 and 0.45kg a.i/ha) on the growth, leaf chlorophyll types and grain yield of soybean c.v. SAMSOY 2. Imazaquin applications had no significant effect on the growth of soybean roots on most of the sampling dates, but pre-and post-emergence applications of imazaquin at 0.30 and 0.45kg a.i/ha reduced soybean root nodules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The appearance of chlorosis in the leaves of imazamox-treated sunflower plants in our study was due to their significantly lower chlorophyll content (Figure 3). This observation is in accordance with the data presented by Alonge (2000) for the decreased chlorophyll a content in imazaquin-treated soybean plants as well as imidazolinine herbicide treated sunflower and wheat plants (Pozniak et al, 2004; Ochogavía et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…The appearance of chlorosis in the leaves of imazamox-treated sunflower plants in our study was due to their significantly lower chlorophyll content (Figure 3). This observation is in accordance with the data presented by Alonge (2000) for the decreased chlorophyll a content in imazaquin-treated soybean plants as well as imidazolinine herbicide treated sunflower and wheat plants (Pozniak et al, 2004; Ochogavía et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the decreased supply of photosynthate to the roots due to totoxic action of atrazine and metribuzin and the direct effects of these herbicides on the growth of Bradyrhizobium in vitro might have resulted in the reduction of functional symbiosis. The data from this study thus supported the concept that the detrimental effect of atrazine and metribuzin is primarily bacterium mediated that resulted in the indirect effects on nodulation and yield (Alonge, 2000). Seed yield increased marginally with 200 and 400 µg.a.i.kg -1 of sulfosulfuron while atrazine and isoproturon, at the same rates significantly (P ≤ 0.05) declined the seed yield compared to control.…”
Section: Iaasupporting
confidence: 75%
“…The ND and 2D rates of the other herbicides, however, did not show any significant effect on photosynthetic pigments at 90 d after seeding the chickpea, as compared with control. Other studies have also shown an inhibition in shoot growth and chlorophyll concentration following pre-emergence and post-emergence applications of four rates of imazaquin to soybean [3]. The 10D rates of each herbicide, in general, showed significant reduction in shoot N at both stages of plant growth.…”
Section: Herbicidal Effects On Chickpea 125mentioning
confidence: 78%